PENGARUH SISTEM BAGI HASIL DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN NASABAH MEMILIH TABUNGAN MUDHARABAH (TABAH) DI BMT NU CABANG BUNGATAN SITUBONDO - Abdul Fatah; Nur Muhammad; Sri Yuniati; Nuri Ma'rifatul Laily (NATUJA: Jurnal Ekonomi Syariah, 2026)
Amid growing competition in Islamic financial institutions, the ability to attract and retain customers has become crucial for the sustainability of products, especially Mudharabah Savings (TABAH) based on the profit-sharing principle. This study aims to examine the effect of profit-sharing system (X1) and service quality (X2) on customers' decisions (Y) to choose TABAH at KSPPS BMT NU Branch Bungatan Situbondo. A quantitative approach with an explanatory design was employed, involving 90 respondents selected through purposive sampling. The questionnaire instrument had been tested for validity and reliability. Data were analyzed using multiple linear regression, t-test, F-test, and coefficient of determination using SPSS. The results show that the profit-sharing system significantly affects customer decisions with a significance value of p = 0.003 < 0.05, and service quality significantly affects customer decisions with p = 0.000 < 0.05. Service quality proved to be the most dominant factor. The coefficient of determination of 0.549 confirms that 54.9% of customers' decisions can be explained by both variables. These findings underscore that the competitive advantage of Islamic financial institutions lies not only in financial returns but also in service quality that fosters trust and customer loyalty.